Variability of sea surface chlorophyll_a concentration in the South Vietnam coastal waters related to enso phenomenon - Tac, Vu Van (Vietnam Journal of Earth Sciences, 2020)
This paper focuses on analyzing the monthly averaged sea surface chlorophyll_a concentration data for 16 years (Jul. 2002 ÷ Sep. 2018), a remote sensing data product of the US National Aeronautics and Space Administration (US NASA), the analyzed results have shown that each occurrence of ENSO phenomenon greatly affects the fluctuation of chlorophyll_a concentration in the South Vietnam‘s coastal waters (SVNC). The monthly averaged chlorophyll_a concentration varies from 0.5 [mg/m3] to 1.1 [mg/m3] (equivalent to 22.4% ÷ 49.3%), while the monthly averaged fluctuation of chlorophyll_a concentration between months is only 0.22 [mg/m3] (equivalent to 9.88%). These fluctuations have a great impact on nutritional resources as well as water quality because chlorophyll_a is a pigment in plankton, which is a criterion to assess the "rich or poor" of nutrition source in seawater. The results of this study are considered as a "small piece" in the overall picture of the impact of ENSO phenomenon on global climate change.